If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2(y + 5) = 4(y + -7) + -1(y + -1) Reorder the terms: 12 + -2(5 + y) = 4(y + -7) + -1(y + -1) 12 + (5 * -2 + y * -2) = 4(y + -7) + -1(y + -1) 12 + (-10 + -2y) = 4(y + -7) + -1(y + -1) Combine like terms: 12 + -10 = 2 2 + -2y = 4(y + -7) + -1(y + -1) Reorder the terms: 2 + -2y = 4(-7 + y) + -1(y + -1) 2 + -2y = (-7 * 4 + y * 4) + -1(y + -1) 2 + -2y = (-28 + 4y) + -1(y + -1) Reorder the terms: 2 + -2y = -28 + 4y + -1(-1 + y) 2 + -2y = -28 + 4y + (-1 * -1 + y * -1) 2 + -2y = -28 + 4y + (1 + -1y) Reorder the terms: 2 + -2y = -28 + 1 + 4y + -1y Combine like terms: -28 + 1 = -27 2 + -2y = -27 + 4y + -1y Combine like terms: 4y + -1y = 3y 2 + -2y = -27 + 3y Solving 2 + -2y = -27 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 2 + -2y + -3y = -27 + 3y + -3y Combine like terms: -2y + -3y = -5y 2 + -5y = -27 + 3y + -3y Combine like terms: 3y + -3y = 0 2 + -5y = -27 + 0 2 + -5y = -27 Add '-2' to each side of the equation. 2 + -2 + -5y = -27 + -2 Combine like terms: 2 + -2 = 0 0 + -5y = -27 + -2 -5y = -27 + -2 Combine like terms: -27 + -2 = -29 -5y = -29 Divide each side by '-5'. y = 5.8 Simplifying y = 5.8
| y=5Inx | | 6.1=7.7-0.8x | | 12y=2x-6 | | 3m+3=2m+4 | | 2(5x-4)=11x | | graphy+9=5(x+6) | | 2x-9=8x+3 | | 1/7(3x+2)-1/5(x+4)=2 | | 14=7x+6-5x | | 5(3x-1)=19 | | x(x-4)=221 | | 4x-3y=26 | | 8u+2=4u-10 | | b-1+3b=22 | | 0.2p-1.8=2.3p-4.5-1.8p | | 0.06x+0.03(100+x)=4.35 | | x^2000+x^1000-2=0 | | 3y^2-11y-10=0 | | 5-3x=3x+15 | | 5-3x=3x-15 | | 6(x+3)=2(x+27) | | 0.007(x+3)=0.008x+0.016 | | 5[7-5(6b)]-7=7[5(7b-6)+4]-50 | | X+3=4x-7 | | x^2000+x^1000-2 | | 11=9x+2-6x | | n-20=-7 | | 4c-2=2 | | 0.04(y-1)+0.08=0.02-0.01(70) | | x÷4=3 | | 5(6-3)=75-5x | | 4x^3+8x^2-9x-18=0 |